2017
DOI: 10.21873/anticanres.11652
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MicroRNAs Involved in Resistance to Sunitinib in Renal Cell Carcinoma Cells

Abstract: These miRNAs may contribute to sunitinib resistance in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 21 publications
3
40
0
Order By: Relevance
“… 6 8 miR-431 is located on chromosome 14q32.2; 9 Pan et al found that miR-431 is a possible novel marker for renal cancer, lung cancer, and melanoma, even at the primary stage of cancer. 10 13 Meng et al 14 investigated that hsa-miR-431-5p was downregulated in the serum of diffuse large B-cell lymphoma patients. Yamaguchi et al 13 found that miR-431 could contribute to chemotherapy resistance in human cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 8 miR-431 is located on chromosome 14q32.2; 9 Pan et al found that miR-431 is a possible novel marker for renal cancer, lung cancer, and melanoma, even at the primary stage of cancer. 10 13 Meng et al 14 investigated that hsa-miR-431-5p was downregulated in the serum of diffuse large B-cell lymphoma patients. Yamaguchi et al 13 found that miR-431 could contribute to chemotherapy resistance in human cancer.…”
Section: Introductionmentioning
confidence: 99%
“… 10 13 Meng et al 14 investigated that hsa-miR-431-5p was downregulated in the serum of diffuse large B-cell lymphoma patients. Yamaguchi et al 13 found that miR-431 could contribute to chemotherapy resistance in human cancer. In addition, Trehanpati et al 15 found that miR-431 was significantly expressed in hepatitis E viral (HEV) infection in liver.…”
Section: Introductionmentioning
confidence: 99%
“…One of the primary reasons for the failure of RCC treatments is that patients with advanced RCC often develop resistance to anti-cancer agents [13]. The matrix metalloproteinases (MMPs), crucial proteolytic proteinases that allow malignant cells to access the vasculature, are a family of zinc-dependent endopeptidases with broad substrate specificities for a variety of extracellular matrix (ECM) and basement membrane proteins [14].…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs play an important role as regulators of gene expression in tumorigenesis, tumor progression, drug resistance, and metastasis ( 13 , 14 ). Thus, we previously generated a sunitinib-resistant RCC cell line, SR-ACHN (sunitinib-resistant ACHN), by continuous treatment with sunitinib to detect candidate miRNAs implicated in the regulation of sunitinib resistance ( 15 ). The aim of this study was to identify miRNAs that suppressed sunitinib resistance via LAMP2 expression using ACHN and SR-ACHN cells.…”
Section: Introductionmentioning
confidence: 99%